2002
DOI: 10.4050/jahs.47.33
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network Based Representation of UH-60A Pilot and Hub Accelerations

Abstract: Neural network relationships between the full-scale, experimental hub accelerations and the componding pilot floor vertical vibration are studied. The present physics-based, quantitative effort represents an initial systematic study on the UH-60A Black Hawk hub accelerations. The NASNArmy UH-6OA Airloads Program flight test database was used. A "maneuvereffect-factor 0,'' derived using the roll-angle and the pitch-rate, was used. Three neural network based representation-cases were considered. The pilot floor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…1. The inputs for the ANFIS are the same parameters that were used earlier 4 for training the neural networks and details are given later in the Results section. The single output of ANFIS is the predicted peak, 4P pilot floor vertical vibration, PVV, of UH-60A helicopter.…”
Section: Proposed Neuro-fuzzy Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…1. The inputs for the ANFIS are the same parameters that were used earlier 4 for training the neural networks and details are given later in the Results section. The single output of ANFIS is the predicted peak, 4P pilot floor vertical vibration, PVV, of UH-60A helicopter.…”
Section: Proposed Neuro-fuzzy Modelmentioning
confidence: 99%
“…It has been shown that neural network based representations can be obtained for the UH-60A pilot vibration and the hub accelerations 4,5,6 . Similarly, tilt-rotor performance and noise were considered using only neural networks, without any fuzzy logic considerations 7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations